Performance comparison of multimedia application over IPv4 and IPv6 network / Ummi Suraya Shaharuddin - Shaharuddin, Ummi Suraya (2016)
As acknowledged, the exhaustion of IP addresses by IANA (Internet Assigned Numbers Authority) is the main reason why world needs to migrate from IPv4 to IPv6. This paper analyzed a performance comparison using Dual Stack Technology based on both Simulator by GNS3 and real Cisco devices. Multimedia streaming from Host to Client scenario was set up and the streaming performance of both IPv4 and IPv6 protocol were compared and analyzed. A comprehensive quantifiers were used to measure the performance between the two such as, RTT - round trip time/delay, for TCP and UDP Result from this analysis can be a benchmark to proof that IPv6 is having a better performance compared to IPv4 based on the Dual Stack Hosts.